2023
DOI: 10.3389/fimmu.2023.1151468
|View full text |Cite|
|
Sign up to set email alerts
|

IL-3 produced by T cells is crucial for basophil extravasation in hapten-induced allergic contact dermatitis

Abstract: Basophils have been recognized as a characterized cellular player for Th2 immune responses implicated in allergic diseases, but the mechanisms responsible for basophil recruitment to allergic skin remain not well understood. Using a hapten fluorescein isothiocyanate (FITC)-induced allergic contact dermatitis (ACD) mouse model, we show that basophils in FITC-treated IL-3-knockout mice are defective in crossing the vascular endothelium to enter the inflamed skin. By generating mice in which IL-3 is selectively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…In line with our report, a recently published scRNA-seq study of an ovalbumin (OVA)-sensitized murine skin model also unexpectedly found that mast cells/basophils, rather than T cells, are the major source of IL4 and IL13 (Xu et al, 2022). Another recent study showed that basophil-mediated type-2 immune response is mediated by IL3-produced by T cells in the hapten-induced ACD mouse model (Hachem et al, 2023). Future studies investigating cellular interactions between basophils and dFBs will advance our understanding of the basophil chemotaxis mechanism and the role of basophils in skin allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our report, a recently published scRNA-seq study of an ovalbumin (OVA)-sensitized murine skin model also unexpectedly found that mast cells/basophils, rather than T cells, are the major source of IL4 and IL13 (Xu et al, 2022). Another recent study showed that basophil-mediated type-2 immune response is mediated by IL3-produced by T cells in the hapten-induced ACD mouse model (Hachem et al, 2023). Future studies investigating cellular interactions between basophils and dFBs will advance our understanding of the basophil chemotaxis mechanism and the role of basophils in skin allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Do basophils interact with CD4 + T cells in skin lesions? A recent murine study revealed that T cells are essential for basophil extravasation in allergic skin inflammation via IL‐3 12 . IL‐3 also induces IL‐4 and IL‐13 secretion from basophils and potentiates the release of proinflammatory mediators and cytokines from basophils 13 .…”
Section: Discussionmentioning
confidence: 99%
“…As for eosinophils, IL-3 plays a key role in basophil survival, migration and activation. Indeed, IL-3 protects basophil from apoptosis in vitro in a Pim1-dependent manner ( 57 ), increases basophil number in the blood during parasite infection ( 34 ), and enables basophil extravasation during allergic contact dermatitis ( 58 ). Moreover, IL-3, alone or in a combination with other molecules, such as anti-FcϵRI mAb, complement component 5a, N-Formylmethionine-leucyl-phenylalanine (fMLP), CCL2 or eotaxin, enhances the expression of various immune mediators important for the function of basophils, such as histamine ( 59 ) or granzyme B ( 60 ).…”
Section: Cellular Targets Of Il-3mentioning
confidence: 99%